The Awareness Degree of the Principles and Applications of Green Chemistry among Students of Scientific Colleges at University of Bisha - Alrawili, Khaled Saleh R; Youssif, Ahmed Elshawadfy; Saeed, Ali Muhammed (Journal of Ecohumanism, 2024)
The study aimed to reveal the awareness degree of the principles and applications of green chemistry among the students of scientific colleges at Bisha University. The descriptive (survey) approach was adopted to achieve the study’s objectives. The sample consisted of (168) male and female students from the scientific sections in the Colleges of (Medicine, Engineering, Applied Medical Sciences, Computers and Information Technology, and Science) at the University of Bisha. A scale of green chemistry awareness principles and applications was built considering the literature on green chemistry. It consisted of (12) principles and (95) applications related to them. The study reached many results; the level of awareness of the principles and applications of green chemistry among science students at the University of Bisha is weak. The students obtained an average of (4.036) of the total score on the scale, which amounted to (12) points, with a percentage of (33.63%). There are no differences between the students’ average scores and the other colleges. There are statistically significant differences at the level of significance (0.01) between the students’ average scores on the scale for only four principles. The study presented many recommendations and suggestions.